2000
DOI: 10.1111/j.1572-0241.2000.02315.x
|View full text |Cite
|
Sign up to set email alerts
|

High frequencies of telomeric associations, chromosome aberrations, and sister chromatid exchanges in ulcerative colitis

Abstract: Our results demonstrate the presence of an unstable genome in UC patients that could be related to the cancer development observed in this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…A possible explanation includes a systemic defect, backed by genomic instability and high frequency of telomeric associations in circulating lymphocytes of UC patients. 67 Additional striking differences were detected when LPT division was analysed by CFDA staining. Regardless of CD2 or CD3 activation, CD LPT vigorously expanded while T cell division was drastically restricted in UC, with less than half of the cells dividing.…”
Section: Discussionmentioning
confidence: 97%
“…A possible explanation includes a systemic defect, backed by genomic instability and high frequency of telomeric associations in circulating lymphocytes of UC patients. 67 Additional striking differences were detected when LPT division was analysed by CFDA staining. Regardless of CD2 or CD3 activation, CD LPT vigorously expanded while T cell division was drastically restricted in UC, with less than half of the cells dividing.…”
Section: Discussionmentioning
confidence: 97%
“…Higher frequencies of chromosomal rearrangements and telomere fusions have also been observed in peripheral blood lymphocytes (PBLs) in UC 14 . This may indicate a global predisposition towards genomic instability in IBD, which could represent a biomarker for increased cancer risk, as has been observed in several other malignant and premalignant diseases, 15–20 including colon cancer 21 and celiac disease 22 .…”
Section: Introductionmentioning
confidence: 84%
“…No studies have been conducted on MN formation in the lymphocytes of patients with UC. However there is one available study which is concerned with sister chromatid exchange (SCE) in lymphocytes, where it was reported that SCE was elevated in the lymphocytes of patients with UC [34]. SCE is another cytological method used to detect chromosomal damage.…”
Section: Discussionmentioning
confidence: 99%